The Leaders across Borders Certification Program—A Systemic Multiple Level Observation of Groups Analysis Approach to Measure Effective Leadership: A Case Study - Hirata-Okamoto, Ricardo; Rangel-Gomez, Maria Gudelia; Guerrero, Robert; Zapata-Garibay, Rogelio; Rosales, Cecilia Ballesteros (Frontiers in Education, 2017)
Leadership measurement, feedback and development have grown in importance for the field of management. The Mexico-US Border defined as the area of land within 100 kilometers (62.5 miles) north and south of the international boundary, shares common challenges, and requires the development of multicultural change agents who conduct binational actions toward the improvement of public health and quality of life of the population in the region. Leaders Across Borders (LaB) was established in 2010 as an advanced certified binational leadership development program aimed at building the capacity of public health, health care and other community sector leaders working to improve the health of the communities in the Mexico–US Border region. Leadership as a social interaction process requires leader skills development to achieve goals promoting unity and reducing polarization to optimize interactions between all resources, thus improving teamwork. Therefore, measurement and feedback model of general values and beliefs that guide effective behavior, not only individual personality assessments need to drive a proactive learning and action plan development to improve interactions in a team, thus optimizing leadership. Starting 2014, we administered a new model named Systemic Multiple Level Observation of Groups (SYMLOG) to measure the values and beliefs that guide the behavior of learners and team facilitators. We also evaluated the effectiveness of each team of the program and established benchmarks and action plans to optimize interactions and communication between all the learners during the 8-month program. This leads to a stronger systemic network upon graduation from the program. The SYMLOG approach measured initial and improved situations of individual leadership and team performance effectiveness because of the LaB Program training and skills development sessions. The SYMLOG also provided positive feedback to each participant, which had a direct impact on the optimization of members´ interactions of all teams, as well as developing effective leadership values and behaviors of participants. This paper presents a case study of this application, the challenges in the design and implementation of the SYMLOG measurement model and the results obtained for last three cohorts 2014-2016 of Leaders Across Borders program.